Proposals for Second Five Year Plan Jails Sector Government of Rajasthan - Planning Commission (Planning Commission, 1955)
Housing of lock-ups has already been included Under the Government Buildings Programme. Rs. 10 lakhs are proposed to be spent during the Second. Plan period. Borstal treatment for juvenile offenders is being proposed. To reclaim, reform and to educate adult offenders and to provide them with technical training such as would enable them to earn an honest living after release, provision has been made for improving the existing arrangements, for the reorganisation of Jail industries and for the prisoners.
Planning Department Government of Rajasthan